The Role Of Corporate Leadership In Increasing Work Motivation At Agafia Boutique Jalan Gegerkalong Hilir No 213 Bandung, West Java - Syaira Natasya (Sean Institute, 2024)
The leadership of a company has a big impact on the work motivation of its employees. Leadership is the ability to persuade and guide others towards certain goals. Motivating employees is just one of the many aspects of a business that effective leadership will consider. This research uses qualitative methodology, collecting information through direct observation and interviews with fifteen Agafia Boutique staff members. By using interactive analytical techniques, researchers can study data while drawing conclusions from their findings and reducing the data. Research findings show that leadership at Agafia Boutique has a significant role in increasing employee motivation. Motivation in the workplace can be improved by leaders in a number of ways, including by creating a happy working atmosphere, recognizing the contribution staff members have made to the business, trusting their skills and rewarding them for success. These factors can be a catalyst to increase employee motivation at Agafia Boutique. Motivated employees will have a positive impact on Agafia Boutique, such as increasing company productivity, ideas for innovation will emerge, and the company will experience significant progress.